A Critical Review on the Book Ibn Khaldon and History - Abolhasan Fayaz Anush (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Persian translation of Ibn Khaldon and History'-a book by Mohammad Talbi (1921-2017); a Tunesian historian and thinker-provide a fortune to Iranian for getting familiar with the author and his thoughts. Although Talbi wrote various works in the field of Muslim thought and history during his life, but a few of his works are translated into the Persian language. Talbi has several articles on Ibn Khaldon life and his Moghaddameh but Ibn Khaldon and History is a single book of Talbi that has been translated and published in the Persian language. After reviewing Ibn Khaldun thought, Talbi asks about the purpose of history. This question inevitably leads to other issues, and finally, Talby comes to the answer: History is inevitably constantly moving towards civilization. Talbi named this prosses: Sonnat Allah. The survey aims to provide a critical assessment of the book and its translation. The most important issue that has been criticized is Talbi Eurocentric historiography.